First Impressions Last? Lay-Judges’ Assessments of Credible Victimhood - Heber, Anita (The British journal of criminology, 2025)
This article explores how Swedish lay-judges assess victims’ credibility in district court. Previous studies have explored how biases and emotional expressions impact credibility assessments. Adding to this, the present study analyses how lay-judges assess courtroom credibility from an intersectional perspective. Based on 24 in-depth interviews with lay-judges, the study explores three intertwined layers of credibility: appearances, narratives and emotions. The analysis concludes that these layers actualize balancing acts for both victims and the lay-judges assessing them. These layers of credibility can compound for victims, making them particularly credible in the eyes of the lay-judges, especially if and when they perform victimhood in line with expectations set by their intersectional characteristics.